Metabolism and Metabolomics of Liver in Health and Disease - Wahli, Walter; Guillou, Hervé (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Women and men have probably never been concerned as much by their health as during this COVID-19 pandemic. In this context, lifestyle habits continue to be promoted as allies for daily prevention against diseases. This is valid also for metabolic diseases, among which many affect the liver and are risk factors for aggravating the disease course of COVID-19. In fact, liver diseases are currently a major global health problem. There is a huge range of liver diseases and non-alcoholic fatty liver disease (NAFLD) is the most common chronic hepatic condition, which in some patients progresses to cirrhosis and liver cancer. Currently, substantial efforts are being made to better understand NAFLD, especially, because there is no U.S. Food and Drug Administration (FDA)-approved pharmacological therapy. To explore this disease, metabolomics is the most recently developed omics technology after genomics, transcriptomics, and proteomics. Metabolomics is the large-scale analysis of molecules, known as metabolites that are intermediate or end products of metabolism found within cells, tissues, and biofluids. This technology has a very high potential to identify biomarker candidates for the future development of new therapeutics. The book features articles that address metabolomics technology and its use to document different liver functions and dysfunctions, with a major focus on NAFLD.